24 Is it feasible to apply the healthcare complaints analysis framework to complex complaints in a paediatric setting?. (22nd November 2019) - Wray, Jo; Williams, Claire; Oldham, Geralyn
Abstract : Introduction: The importance of improving the analysis of complaints about poor healthcare experiences is well recognised but often not addressed. The Healthcare Complaints Analysis Tool (HCAT) was developed to improve the extraction of data from formal complaints to facilitate monitoring and learning, but this has been predominantly applied in adult settings with less complex complaints. Our objective was to explore the utility of HCAT in a specialist paediatric hospital where the number of formal complaints is relatively small but often extremely complex. Methods: Ten written complaints were retrospectively scored using HCAT. Each complaint was individually reviewed to assess whether or not the scoring framework was applicable and to identify any challenges with extracting the information. We also looked at the response provided by the organisation to the complainant. Results: All elements of the HCAT scoring framework could be applied to the complaints. Communication (n=26;36%) and safety (n=13;18%) were the domains with the greatest number of problems and highest levels of severity and overall harm but in the domains of environment (n=2;3%) and respect and patient rights (n=4;6%) the number of problems was low. Scoring the responses as well as the complaints revealed instances where the response suggested more problems and higher levels of severity than initially identified by the complainant, as well as instances where a seemingly serious problem in a complaint was not supported by the evidence. On average it took 25 minutes to score each complaint and corresponding response. Conclusion: It is feasible to use HCAT and the framework can be easily applied. Our use of HCAT for scoring the response is a novel application of HCAT which we believe will be important for institutional learning. Training now needs to be implemented, the inter-rater reliability of HCAT assessed and a system developed for ensuring timely organisational learning.